(untitled) (Sustainability in Debate, 2021)
Frequent cases of water scarcity in Brazil reveal a water governance and administration crisis. During the water crisis (2013-2016), the São Paulo Metropolitan Region experienced a disaster scenario. This article analyses how it was constituted as a socially constructed disaster episode. A case study was carried out in the Novo Recreio neighbourhood (Guarulhos, SP) through ethnographic observations, interviews, and newspaper articles. The results were analysed based on the Pressure and Release Model (PAR). It was concluded that the water crisis period in SPMR has disproportionately affected the Guarulhos population, especially in Novo Recreio. Furthermore, the study demonstrated that public policies and the neighbourhood’s territorial formation are related to its population’s current frail living conditions and increased socio-environmental vulnerability in the face of continuous water scarcity, thus corroborating the social construction of the risk of water scarcity.